The philosophy of psychology - Botterill, George (Cambridge University Press, 1999)
What is the relationship between common-sense, or 'folk', psychology and contemporary scientific psychology? Are they in conflict with one another? Or do they perform quite different, though perhaps complementary, roles? George Botterill and Peter Carruthers discuss these questions, defending a robust form of realism about the commitments of folk psychology and about the prospects for integrating those commitments into natural science. Their focus throughout the book is on the ways in which cognitive science presents a challenge to our common-sense self-image - arguing that our native conception of the mind will be enriched, but not overturned, by science. The Philosophy of Psychology is designed as a textbook for upper-level undergraduate and beginning graduate students in philosophy and cognitive science, but as a text that not only surveys but advances the debates on the topics discussed, it will also be of interest to researchers working in these areas.